Importance of Contextual Factors When Measuring Work Outcome in Ankylosing Spondylitis: A Systematic Review by the OMERACT Worker Productivity Group. Issue 9 (September 2015) - Stolwijk, Carmen; Castillo‐Ortiz, José‐Dionisio; Gignac, Monique; Luime, Jolanda; Boonen, A.; for the OMERACT Worker Productivity Group; Lacaille, Dianne; Fautrel, Bruno; Tang, Ken; Verstappen, Suzanne; Escorpizo, Reuben; Tugwell, Peter; et al.
<x xml:space="preserve">Abstract</x> Objective To review the literature on contextual factors (CoFas) and their relationship to work outcomes in individuals with ankylosing spondylitis (AS). Methods Articles that quantified the relationship between CoFas and employment status, sick leave, or presenteeism in individuals with AS were systematically identified. CoFas were classified into 5 domains for personal factors and 8 domains for environmental factors. We defined criteria for best‐evidence synthesis for each CoFa domain based on the number of studies exploring that domain, and the quality of evidence of individual studies based on the risk of bias, adjustment of multivariable analyses for disease activity and physical function, and sample size. Results Twenty‐five studies met our inclusion criteria: 20 addressed employment status, 6 examined sick leave, and 3 presenteeism. For employment, there was strong evidence for the role of age, moderate evidence for related skills/abilities, the absence of work accommodations, the nature of work and absence of workplace support, and poor evidence for the role of marital status. Evidence was insufficient for sex, education, and physical environment. For sick leave and presenteeism there were too few studies to perform a best‐evidence synthesis for the role of CoFas. Conclusion Using a newly proposed set of criteria for determining the best‐evidence of the association between CoFa domains and work outcome, the following factors emerged: age, related skills/abilities, work accommodations, nature of work, and workplace support. In addition to disease‐related variables, these CoFa domains seem important to include when designing and interpreting studies on work outcomes.